Ionel Bratianu Romania - Hitchins, Keith 1931- (Haus histories, 2011)
Ionel Bratianu, a major political force both in and out of power, was responsible for his country's presence at the Paris Peace Conference Romania came to Paris as a minor member but Bratianu felt that Romania had made sufficient sacrifices and had allied itself with the right parties to be heard and rewarded. The Paris Conference was also a culmination of Bratianu's life-long quest to Westernise and modernise Romania and to bring together all Romanians in a national state (particularly those in Transylvania, Bukovina and Bessarabia).